Household Socioeconomic Status and Antenatal Care Utilization Among Women in the Reproductive-Age - Sui, Yubing; Ahuru, Rolle Remi; Huang, Kaishan; Anser, Muhammad Khalid; Osabohien, Romanus (Frontiers in Public Health, 2021)
We assessed the impact of wealth and selected socio-demographic on antenatal care (ANC) utilization among 900 women within the reproductive ages across eight rural communities in Delta State, Southern part of Nigeria. Women on the highest wealth quintile were 25.2 times more likely to make 4-7 ANC visit (aOR: 25.2, 95 per cent CI: 3.13-203.33) and 2.6 times more likely to meet the recommended number of 8 ANC visits (aOR: 2.6, 95 per cent CI: 0.63-3.86). This finding has an implication for the free maternal care policy currently in operation in Delta State. It implies that the policy has not succeeded in redressing problems of financial barriers in access to maternal care. The lesson, therefore, is that the policy of free maternal care is not enough, but if the government desires to maximize the dividend from the policy, then it must go beyond absolving pregnant women of ANC charges to provide another form of supports.